Legal Protection for Members of The Sharia Savings and Loan Cooperative - Rohmat Soekarno; Isman Isman; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2025)
This article examines legal protection for members of Islamic savings and loan cooperatives in the event of default due to mismanagement, resulting in members being unable to withdraw their savings due to a lack of funds. The discussion focuses on the role of law in guaranteeing the restoration of members' rights and the need for legal certainty so that disputes do not drag on and do not only depend on the cooperative's internal mechanisms. The research uses a normative-empirical legal approach with qualitative analysis that links legal norms and institutional practices. The normative study is based on Law Number 25 of 1992 concerning Cooperatives and PermenKopUKM Number 8 of 2023, as well as the principles of muamalah in sharia economic law as an ethical and substantive framework. The analysis shows that, normatively, the management bears responsibility for losses incurred by the cooperative due to errors or negligence. However, the implementation of protection for members remains weak due to limited supervision, low transparency in reporting, weak auditing and administrative evidence, and the dominance of internal settlements that are not always independent. The absence of a cooperative deposit guarantee scheme increases members' legal uncertainty regarding their deposit rights and prolongs the recovery process. From a sharia perspective, this condition contradicts the principle of amanah and the objective of asset protection (hifz al-mal), thus requiring the strengthening of governance and accountability mechanisms. This article emphasizes the importance of effective supervision, adequate access to information for members, confirmation of management accountability, and enforceable dispute resolution mechanisms to ensure fair legal protection and certainty.